Changing places: Landscape and mortuary practice in the Irish Middle Bronze Age - Cross, Sarah (My University, 2000)
This thesis explores an Irish Middle Bronze Age landscape using quantitative spatial analysis as a starting point for broader contextual discussion. The main data set is the distribution of a concentration of ring ditches, which are one end product of a complex burial rite. The concentration was formed throughout the second millennium BC. Other data on terrain variation and change was also important. Three statistical techniques are used to examine clustering--kernel smoothing, k-functions and raised incidence modeling. In addition, Site Catchment Analysis has been upgraded to explore terrain factors in a standardised, statistically robust fashion. The results are discussed under the headings: scale, terrain sensitivity, integration and tempo. The pattern is unusually clustered at many but not all scales. Important concentrations of ring ditches were sited in the previously unused foreshores of small glacial lakes. Further investigation of these foreshores produced an Late Bronze Age date for a larger, newly identified, burial monument type. I conclude that an iterative process, with no central design, but potentially based on kin groups, formed this concentration of sites. Further, the availability of well-drained soil is an important factor in the distribution of sites. There is a separation of domestic activities, burial, and other community rituals. However, this is not a 'ritual landscape'. In the Late Bronze Age this separation became more pronounced, possibly indicating increased social centralisation. These landscape changes may also indicate a changed role for the area in regional trading networks. The thesis contributes to an understanding of increased social complexity in a period of environmental change. It also indicates the value of quantitative landscape analysis in such discussions.
Keywords: Anthropology; Anthropology